Implementation of a quality management system for decentralized manufacturing of cell and gene therapy products - technical and regulatory considerations - von der Leyen, Heiko; Delgado, Julio; Mazouz, Chaya; Schmitt, Michael; Caplan, Vered (Frontiers in Medicine, 2025)
Decentralized manufacturing has emerged as a promising approach to improve the accessibility and scalability of cell and gene therapy products, particularly for autologous treatments. This paper proposes a comprehensive Quality Management System (QMS) framework tailored to decentralized cell therapy manufacturing, integrating current Good Manufacturing Practice (cGMP) principles and regulatory oversight through a centralized Control Site model. The Control Site serves as the regulatory nexus, maintaining POCare Master Files and ensuring consistency across multiple decentralized manufacturing sites. Decentralized manufacturing has the potential to facilitate accessibility for cell and gene therapies. The proposed model leverages automated, closed-system technologies to minimize process variability and hardware deviations, thereby enhancing product quality and regulatory compliance. The Control Site holds functional roles like primary focus point for interaction with regulatory agencies, provision of quality assurance, qualified person (QP) and oversight systems. It also maintains the POCare Master File for the individual POCare GMP manufacturing sites. A standardized GMP manufacturing platform (e.g., deployable as prefabricated units allowing quick expansion) and an overarching training platform should guarantee quality standards. Key regulatory expectations will be discussed, e.g., the demonstration of consistency and comparability, the central role of QP (as proposed in the context of the European Commission’s Pharma strategy), and the Control Site as single point of contact for competent authorities. This approach aims to streamline cell therapy production at or near point of care, supporting rapid and cost-effective clinical implementation.